Work and prison: the profile of the prisoners at Belém's Penitentiary Progression Center, Pará State, Brazil (Research, Society and Development, 2020)
The objective is to identify the characteristics of the prisoners who carry out work activities outside the prison house at Belém's Penitentiary Progression Center. It was used documentary research and data collection in the Superintendency of the Penitentiary System of the State of Pará regarding the population of the Penitentiary Progression Center Belém, where a quantitative descriptive analytical study was carried out. The study population is 163 inmates stationed at Belém's Penitentiary Progression Center in August 2017, male, who are inserted in prison work. The statistical technique used was Descriptive Analysis. It appears that all prisoners are predominantly in the age group 25-34 years, black in color / race (black / brown), with incomplete elementary education, who mainly committed the crime of theft / robbery, following the profile of the Pará prison population in general and the profile of the national prison population, differing in two aspects: education, which in Brazil the majority of the prison population has complete elementary education and in Pará and at the Penitentiary Progression Center of Belem, the majority have incomplete elementary education and as to the type of crime committed, that at national level the predominant crime is the crime of drug trafficking while in the State of Pará and in the penal house Belém's Penitentiary Progression Center is a crime against property, more precisely the crime of theft / robbery. Criminal recidivism is less when the prisoner is inserted in prison work.